2021
DOI: 10.1038/s41699-021-00244-x
|View full text |Cite
|
Sign up to set email alerts
|

2D-MoS2 goes 3D: transferring optoelectronic properties of 2D MoS2 to a large-area thin film

Abstract: The ongoing miniaturization of electronic devices has boosted the development of new post-silicon two-dimensional (2D) semiconductors, such as transition metal dichalcogenides, one of the most prominent materials being molybdenum disulfide (MoS2). A major obstacle for the industrial production of MoS2-based devices lies in the growth techniques. These must ensure the reliable fabrication of MoS2 with tailored 2D properties to allow for the typical direct bandgap of 1.9 eV, while maintaining large-area growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Several studies have suggested that ROS generation and oxidative stress production may be one of the underlying mechanisms, leading to nanoparticle-induced cytotoxicity in different cell types [37][38][39][40]. We analyzed the formation of reactive oxygen species in response to MoS 2 , and found a significant production of ROS in cells at higher doses of MoS These results are also correlated with our result of the cytotoxic effect of particles and could be the cause of cell death seen at higher doses.…”
Section: Effect Of Mos 2 On the Production Of Ros In A549 Cellssupporting
confidence: 86%
“…Several studies have suggested that ROS generation and oxidative stress production may be one of the underlying mechanisms, leading to nanoparticle-induced cytotoxicity in different cell types [37][38][39][40]. We analyzed the formation of reactive oxygen species in response to MoS 2 , and found a significant production of ROS in cells at higher doses of MoS These results are also correlated with our result of the cytotoxic effect of particles and could be the cause of cell death seen at higher doses.…”
Section: Effect Of Mos 2 On the Production Of Ros In A549 Cellssupporting
confidence: 86%
“…13 Among different layered TMDs, molybdenum disulfide (MoS 2 ) has gained tremendous attention owing to its fascinating properties such as ease of synthesis, high catalytic properties, exceptional on/off ratio, satisfactory biocompatibility, and enormous direct band gap of 1.8 eV for the monolayer. 14,15 MoS 2 has achieved prime progress in the field of optoelectronics, 4,16 energy storage 17 and conversion, 18 hydrogen evolution reaction (HER), 19,20 and next-generation switches. 21,22 Moreover, MoS 2 layers are often associated with crystal-dependent fluorescence 23 or the ability to quench fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 has achieved prime progress in the field of optoelectronics, 4,16 energy storage 17 and conversion, 18 hydrogen evolution reaction (HER), 19,20 and next-generation switches. 21,22 Moreover, MoS 2 layers are often associated with crystal-dependent fluorescence 23 or the ability to quench fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, various methods have been developed to overcome these drawbacks, including magnetron sputtering, 32 sulfurization of Mo thin films, 29 or ionized jet deposition (IJD). 38 Here, the conventional CVD method has been employed to synthesize the three-dimensional tetrahedral arrangement of micrometer-sized MoS 2 thin films. We also noticed that many works have been published regarding the growth dynamics and various applications of tetrahedral microstructures of MoS 2 in the past few years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, various methods have been developed to overcome these drawbacks, including magnetron sputtering, sulfurization of Mo thin films, or ionized jet deposition (IJD) . Here, the conventional CVD method has been employed to synthesize the three-dimensional tetrahedral arrangement of micrometer-sized MoS 2 thin films.…”
Section: Introductionmentioning
confidence: 99%